Dependable Contact Related Parameter Extraction in Graphene–Metal Junctions. (6th September 2020) - Gahoi, Amit; Kataria, Satender; Driussi, Francesco; Venica, Stefano; Pandey, Himadri; Esseni, David; Selmi, Luca; Lemme, Max C.
Abstract: The accurate extraction and the reliable, repeatable reduction of graphene–metal contact resistance ( R C ) are still open issues in graphene technology. Here, the importance of following clear protocols when extracting R C using the transfer length method (TLM) is demonstrated. The example of back‐gated graphene TLM structures with nickel contacts, a complementary metal oxide semiconductor compatible metal, is used here. The accurate extraction of R C is significantly affected by generally observable Dirac voltage shifts with increasing channel lengths in ambient conditions. R C is generally a function of the carrier density in graphene. Hence, the position of the Fermi level and the gate voltage impact the extraction of R C . Measurements in high vacuum, on the other hand, result in dependable extraction of R C as a function of gate voltage owing to minimal spread in Dirac voltages. The accurate measurement and extraction of important parameters like contact‐end resistance, transfer length, sheet resistance of graphene under the metal contact, and specific contact resistivity as a function of the back‐gate voltage is further assessed. The presented methodology has also been applied to devices with gold and copper contacts, with similar conclusions. Abstract : The accurate extraction and the reliable, repeatable reduction of graphene–metal contact resistance are still open issues in graphene technology. Clear procedures for reliably extracting relevant contact parameters that consider the position of the Fermi level in graphene are proposed here. The methodology is demonstrated for nickel, gold, and copper contacts, with similar conclusions.